Public policies for occupational safety and health in Brazil - dos Santos, Claudio José; Almeida, Ildeberto Muniz de; Fischer, Frida Marina (FapUNIFESP (SciELO), 2025)
This study aimed to systematize federal public policies related to occupational safety and health (OSH) in Brazil, focusing on the prevention of occupational diseases and accidents, the promotion of safe work environments, and social protection for workers, in force in Brazil in 2023. The documentary research was conducted in three stages: exploratory research and data collection, systematization, and analysis. Data collection was carried out on official platforms indexing normative instruments, as well as programs or plans instituted by the federal government, using complementary data triangulation strategies. Nine OSH public policies were identified, organized into five thematic categories: Social Security; Labor and Employment; Health; Management; and Inspection and Regulation. Each category encompasses specific strategies to protect workers and promote safe workplaces. In summary, Brazil has adopted a series of governmental efforts to protect workers, expanding protective measures over the past decades. However, there is a need for institutional redesign to minimize the isolation of the identified policies and to carry out their monitoring and evaluation.